Biochemical markers of ovarian reserve evaluation (review) - A S Gasparov (Гинекология, 2014)
A systematic analysis of data available in the current literature to assess ovarian reserve. Made an attempt to assess the specificity and accuracy of these markers and stress tests depending on epiopatogeneticheskih factors leading to a decrease in ovarian reserve.